The Influence of Peer Groups, Economic Literacy, and E-Commerce Utilization on Impulse Buying with Lifestyle as a Moderating Variable: A Case Study in Universitas Negeri Surabaya - Destin Siti Nur Haliza; Jun Surjanti; Tri Sudarwanto (Journal of Education and Learning Research, 2026)
This study examines the influence of peer groups, economic literacy, and e-commerce utilization on impulse buying, with lifestyle as a moderating variable, among undergraduate students of the Faculty of Economics and Business at the State University of Surabaya. The background of this research lies in the growing trend of impulsive consumption among students in the digital marketplace era, which raises concerns about financial behavior and self-control. The study aims to analyze how social interaction, economic understanding, and digital shopping platforms shape impulse buying behavior. A quantitative approach was employed using SEM-PLS analysis with SmartPLS 4. The sample consisted of 388 students selected through purposive sampling based on specific criteria. The results show that peer influence has a negative and significant effect on impulse buying, emphasizing the importance of social dynamics in purchasing decisions. Economic literacy does not significantly affect impulse buying, suggesting that knowledge alone does not guarantee prudent financial behavior. E-commerce utilization has a negative and significant effect, particularly through promotional stimuli that trigger impulsive purchases. Lifestyle moderates the effects of peer influence and e-commerce utilization, indicating that disciplined financial lifestyles help reduce impulsive tendencies. In conclusion, addressing impulse buying requires a holistic approach involving social influence, financial education, and awareness of technology-driven consumption patterns.